2016
DOI: 10.1080/02688697.2016.1208806
|View full text |Cite
|
Sign up to set email alerts
|

The use of atorvastatin for chronic subdural haematoma: a retrospective cohort comparison study

Abstract: Chronic subdural haematoma (CSDH) is a common neurosurgical condition. Burr-hole for drainage is an effective treatment. However, recurrence can be up to 8-33% and is associated with morbidities and mortalities. The underlying pathogenesis was postulated to be localised inflammation and pathological aberrant vessels formation. Atorvastatin, an HMG-CoA reductase inhibitor, is a type of lipid-lowering medication. In animal studies and a preliminary clinical trial, Atorvastatin was shown to be effective in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 24 publications
2
46
0
4
Order By: Relevance
“…1). Of the included studies, 2 studies were retrospective studies [18,19] and the other 1 [13] was a prospective study, and 2 studies [13,18] were performed in China, the rest 1 [19] was in Hong Kong, China. More relevant information was shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Of the included studies, 2 studies were retrospective studies [18,19] and the other 1 [13] was a prospective study, and 2 studies [13,18] were performed in China, the rest 1 [19] was in Hong Kong, China. More relevant information was shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another retrospective study showed that the improvement rate of hematoma at third months after atorvastatin administration was 75% for the atorvastatin group versus 42% for the control group; however, the result did not have any statistically significant difference ( P  = .0977). [19] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies have suggested efficacy of atorvastatin as a conservative treatment option in CSDH with complete haematoma resolution within 6 months in two studies, although patient numbers only totaled 31 [122, 123]. Reduced need for surgical intervention with atorvastatin was also identified by Chan et al in a study on 24 patients [124]. This was supported by a prospective placebo-controlled trial on 80 CSDH patients showing reduction in surgical intervention in patients on atorvastatin; however, the paper was subsequently retracted with a damning admittance that the results were misleading and exaggerated with serious errors in data analysis [125, 126].…”
Section: Pharmacotherapymentioning
confidence: 97%